2021
DOI: 10.22541/au.162152429.96552508/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Advances and highlights in biomarkers of allergic diseases

Abstract: Allergic diseases include asthma, atopic-dermatitis, allergic-rhinitis, drug hypersensitivity and food-allergy. During the past years, there has been a global outbreak of allergic diseases, presenting a considerable medical and socioeconomical-burden. A large fraction of allergic diseases is characterized by a type-2 immune response involving Th2 cells, type-2 innate lymphoid cells, eosinophils, mast cells, and M2 macrophages. Biomarkers are valuable parameters for precision medicine as they provide informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Given the complicated cross-reactions of allergic sensitization, studies to explore the associations between various allergens and clinical symptoms using machining learning methods, such as network analysis or latent class analysis, have been emerging as a hot topic. 28 , 29 However, most of them were performed in European countries, 11 , 12 and the evidence from the Asia area was scarce. China has the largest population around the world and wide geographical distribution in Asia, which results in significant individual heterogeneity of the associations between sensitization panels and clinical performance.…”
Section: Discussionmentioning
confidence: 99%
“…Given the complicated cross-reactions of allergic sensitization, studies to explore the associations between various allergens and clinical symptoms using machining learning methods, such as network analysis or latent class analysis, have been emerging as a hot topic. 28 , 29 However, most of them were performed in European countries, 11 , 12 and the evidence from the Asia area was scarce. China has the largest population around the world and wide geographical distribution in Asia, which results in significant individual heterogeneity of the associations between sensitization panels and clinical performance.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, GO enrichment analysis showed that the TMGs were significantly enriched in immune inflammatory response-related terms including regulation of MHC class II biosynthetic process, immune response, immunoglobulin production and T cell-mediated cytotoxicity, antigen processing and presentation, and regulation of inflammatory response. Immune inflammatory response is one of the key links of allergic diseases [38]. These findings suggest that allergic diseases may participate in the development of KC through the immune inflammatory mechanisms.…”
Section: Discussionmentioning
confidence: 86%
“…Atopic dermatitis (also known as atopic eczema), food allergies, asthma, and allergic rhinitis are the most common allergy-related diseases with similar epigenetic and physiopathological characteristics [22,23]. Numerous experimental and clinical studies have shown that the poor prognosis of atopic dermatitis and food allergies in early life greatly exacerbates the occurrence of later asthma and allergic rhinitis [1][2][3][4]24].…”
Section: Discussionmentioning
confidence: 99%